Оценка точности определения ориентации транспортного средства с помощью параметров Родрига-Гамильтона, вычисляемых реверсным методом - Кононенко, В. А. (НТУ "ХПИ", 2007)
The article presents a method and results of comparison of two integration algorithms of Rodrig - Hamilton parameters in an on-board computer. It is shown that a miscalculation of the integration with the help of a reversible algorithm is proportionate to h5, where h is a time step of a pickup of information from sensors.
Keywords: навигационные системы; угловая ориентация корпуса; гиростабилизированные платформы; системы курсокреноуказания; датчики угловой скорости; реверсный алгоритм